Concerns education of logical thinking at mathematic lessons at primary school in Lithuania in the 6–9 decades of the XX century - Ažubalis, Algirdas (Lietuvos matematikos rinkinys, 2005)
At that time in pedagogical periodic editions there appearde 11 articles about education of logical thinking at mathematic lessons at primary school. 3 articles mentioned were translated from Russian. The other articles were written by Lithuanian teachers that worked at high and secondary schools. This is an evidencing proof that this problem attracted much attention.